Irony Analysis of Memes on Instagram Social Media - Widia Lestari (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2019)
This study disscused the irony in memes on Instagram. The memes were selected by selecting some accounts on Instagram. The aims of this study are to identify the types of irony in meme and to describe the meaning of irony used in memes on Instagram. In conducting this research, the methodology used is descriptive method by Creswell (2008). Theory of types of irony by Perrine (1966) and theory of meaning by Leech (1981) are used to do the analysis. The result of this research shows that there are twenty six verbal irony and four situational irony. Verbal irony in memes can attract the readers interest , and situational irony gives funny effects because of discrepancy between appearance and reality, or between expectation and fulfillment. Verbal irony and situational irony found on the Instagram are illustrated through the utterances in memes, and these memes have implicit meaning (non-literal meaning). How the readers understand the memes depends on their culture, time, and individual experience. Besides, the readers can get the meaning of memes if they compare the memes with the topic that has been viral their life.